Examining the Impact of Training and Development on Employee Performance at Uganda National Airlines Company Limited - Tahidi Judith Natasha (Uganda Christian University, 2024)
The research examined the impact of training and development on employee performance at Uganda National Airlines company Limited. The study used a cross-sectional approach, combining both qualitative and quantitative methods. Cross-sectional studies provide a snapshot of a particular aspect within a population at a single point in time, offering a simple form of descriptive or observational epidemiology conducted on representative samples. A descriptive design was employed, with 53 respondents selected from Uganda Airlines. Employees were chosen randomly, and those who agreed to participate completed questionnaires and were interviewed along with the company's administrators. The results revealed that training positively impacts employee performance, and management should enhance training programs to improve employees; job satisfaction.
Undergraduate research